A TUTELA JURÍDICA DO PANTANAL E A COOPERAÇÃO INTERNACIONAL NA ÉPOCA DO ANTROPOCENO - Rodrigo de Oliveira Ferreira (2022)
The world is experiencing an environmental crisis, marked by the development model adopted by humanity over the centuries and whose consequences mark the Anthropocene epoch. The Pantanal, a wetland of international interest, is suffering the consequences of this crisis. This biome, which covers the territories of Brazil, Bolivia and Paraguay, is of great importance for maintaining the environmental balance of the region, thus evidencing the great importance and need to protect and conserve it for present and future generations, in a cooperative action between the nations that shelter it. In this sense, this Master's thesis explores the issue related to the recognition of the right to the environment and sustainable development as human rights, aiming to answer the following question: how to safeguard human rights, notably the human right to the environment and sustainable development, using international cooperation, through the legal protection of the Pantanal in the context of the Anthropocene? Therefore, its specific objectives are: to describe the scenario of global environmental crisis and the Pantanal; examine third-generation human rights, especially to the environment and sustainable development; highlight the importance of international cooperation for the protection of the Pantanal as a wetland and verify the international and regional legal protection of the Pantanal. In order to achieve these objectives and answer the problem raised, the post-positivist epistemological paradigm is adopted. The theoretical and methodological focus is dogmatic, the method is deductive, the research is exploratory, descriptive with documental, bibliographical and of legal norms.